#### Answer

{1}

#### Work Step by Step

3(5 - x) = 4(2x + 1)
Step 1 : Use distributive property
3.5 - 3x = 4.2x + 4
simplify
15 - 3x = 8x + 4
Step 2 : Collect variable terms on one side and constants on the other side.
subtract 8x from both the sides
15 - 3x - 8x = 8x + 4 -8x
Simplify
15 - 11x = 4
subtract 15 from both the sides
15 - 11x -15 = 4 -15
-11x = -11
Divide both the sides by -11
$\frac{-11x}{-11}$ = $\frac{-11}{-11}$
x = 1
Now we check the proposed solution, 1 , by replacing x with 1 in the original equation.
Step 1: the original equation 3(5 - x) = 4(2x + 1)
Step2: Substitute 1 for x
3(5 - 1) = 4(2.1 + 1)
Step 3: Multiply 2.1 = 2
3(5-1) = 4(2+1)
Step 4: Solve
3(4) = 4(3)
Multiply 3(4) = 12, 4(3) = 12
12 = 12
Since the check results in true statement, we conclude that the solution set of the given equation is {1}